The NAVETA obesity consensus tool: a multidimensional framework for clinical and patient-reported outcome assessment - Mercadal-Orfila, Gabriel; Lluch-Taltavull, Josep; Cuatrecasas, Guillem; García, José María; Maestre-Fullana, María Antonia; Herrera-Pérez, Salvador (Frontiers in Endocrinology, 2026)
BackgroundObesity is a chronic, multifactorial, and relapsing disease that profoundly impairs physical, psychological, and social functioning, leading to substantial deterioration in health-related quality of life (HRQoL). Despite growing evidence on the clinical and organizational value of patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs), their systematic integration into obesity care—particularly within the Spanish healthcare system—remains limited.ObjectiveTo develop the NAVETA Obesity Consensus Tool, a multidisciplinary, consensus-based framework that standardizes the multidimensional assessment of individuals living with obesity by integrating validated PROMs, PREMs, and clinical indicators within a digital, value-based healthcare (VBHC) model.MethodsBetween October 2023 and January 2024, a multidisciplinary panel of experts in endocrinology, nutrition, bariatric surgery, hospital pharmacy, and psychology conducted a structured, iterative consensus process following modified Delphi principles. The development included a systematic literature review, expert scoring of candidate measures, and iterative feedback meetings. Feasibility, scientific validity, and patient relevance were evaluated in collaboration with a national patient association.ResultsThe final framework integrates two complementary domains (1): clinical and physiological variables organized into four categories—clinical, surgical, pharmacological, and nutritional–behavioral—and (2) patient-reported measures encompassing a standardized set of ten validated instruments in Spanish. The proposed PROMs/PREMs set captures key dimensions of obesity care, including quality of life (Moorehead–Ardelt QoLQ), mental health (PHQ-9), sleep quality (STOP-BANG, ISI), dietary adherence (MEDAS), pharmacological satisfaction and adherence (TSQM, MMAS-8), perceived discrimination (MSPD), stigma (SSI), and patient experience (IEXPAC).ConclusionsThe NAVETA Obesity Consensus Tool represents the first consensus-based, patient-centered framework for standardized outcome assessment in obesity care in Spain. By combining validated PROMs, PREMs, and clinical variables within a digital platform, it provides a structured foundation for individualized follow-up, real-world data generation, and benchmarking across centers. This initiative supports the transition toward precision and value-based obesity management—particularly in the context of GLP-1 receptor agonist therapy—and lays the groundwork for a national outcome-based registry aligned with international standards.